Efeito dos prebióticos inulina HP e oligofrutose sobre a absorção intestinal de ferro e morfometria do duodeno e cólon de ratos em fase de crescimento - Freitas, Karine de Cássia [UNIFESP] (2009)
Background: Considering the prebiotic effects in the biovailability of minerals, it is important to evaluate the effect on the absorption of iron. Objectives: To evaluate the effect of HP inulin, oligofructose and synergy1, on the intestinal absorption of iron, food intake, body growth, cecal pH and weight of the intestine of rats in recovery from anemia. Methods: Wistar rats (n=47) were fed with AIN93-G diet without iron for induction of iron deficiency anemia. At the 36 days of life, the anemic rats were divided into four groups: 1) Inulin HP group; 2) Synergy1 group; 3) Oligofructose group, all with 100 g of the respective prebiotic per kg of diet and 4) Control group, in which the prebiotic was replaced by corn starch. In all diets were added 25 mg of iron elemental/kg of diet to lead to recovery of the anemia. Results: The medians (percentiles 25 - 75) of hemoglobin in g/dL, in the last period, in the inulin HP, synergy1, oligofructose and control group were, respectively: 9.8 (9.4 - 9.9); 8.3 (8.1 - 9.2); 10.0 (9.0 - 11.4) and 7.7 (7.2 - 8.1) (p≤0.001), with a statistically significant difference between the oligofructose and control, and HP inulin and control groups. The apparent absorption confirmed this result. The four groups showed an increase of weight and body length and of the consumption of diet similar. The intestinal weight and the cecal pH were significantly different between the groups consuming prebiotics and the control group. Conclusions: Inulin HP and oligofructose increase the intestinal absorption of iron in rats, which can contribute to the optimization of the absorption of iron in food.